THE PSYCHOLOGICAL IMPACT OF LOAD SHEDDING AND POWER OUTAGES ON PAKISTANI HOUSEHOLDS (The Research of Medical Science Review, 2025)
Background: In Pakistan, load shedding and power outages are chronic issues, drastically impacting households and their psychological well-being. The electric disruption leads to increase in stress, frustration and emotional pain, yet most of the psychological effects remain unexplored. Aim: To understand the emotional and psychological responses Pakistani households undertake due to frequent load shedding and its impact on mental health. Method: A qualitative thematic analysis design was used to capture participants’ lived experiences. Using purposive sampling, 300 household members aged 25-55 years from urban and semi-urban areas affected by load shedding for at last two years were recruited. Emotionally distressing events, coping strategies, and daily mundane disruptions to the interviews were the focus of the in-depth semi-structured interviews. Systematic searching of recurring themes was conducted with the help of NVivo software that aided with thematic coding and pattern searching. Results: The constant power cuts have been shown to increase the stress level and sleep deprivation, aggravation, social withdrawal, and emotional burnout. Worsening of mental health conditions among participants was expressed as increased difficulty in fulfilling family’s basic daily needs, work obligations, and strained interpersonal relations. Strategies employed to cope with these need such having reliable sources of power, changing timing of tasks, and having increased psychological readiness were not very effective. The study has strengthened the evidence that chronic shortages of electricity leads to poor psychological health and negative affects on family relations. Conclusion: The incessant power outages have a significant impact on the state of mental well-being, which indicates the need for policy formulation to treat these psychological issues. The socio-emotional cost of the outages must be addressed through facility construction, along with specific psychological help.